2021
DOI: 10.47203/ijch.2021.v33i02.023
|View full text |Cite
|
Sign up to set email alerts
|

Depression, its correlates and quality of life of undergraduate medical students in the Kumaon region of Uttarakhand state, India

Abstract: Background: Medical students are future health care providers and experience a lot of stress during their training years. They are more likely to suffer depressive disorders than the general population and have a poorer quality of life. Objectives: To determine the prevalence of depressive disorder, its correlates and quality of life of medical students studying at a medical college in North India. Methods and material: It was a cross sectional study which included all the students enrolled at the study medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(23 reference statements)
0
7
1
Order By: Relevance
“…The mean age of high school students ranged from 13.2 (± 2.1) 70 to 16.9 (± 1.2) years 92 , while the mean age of university students ranged from 19.0 (± 1.1) 63 to 22.8 (± 3.0) years 63 . Most of the studies included a sample of medical students 63 65 , 67 , 76 , 79 , 81 , 82 , 87 , 89 , 93 , 96 nursing students 80 , 95 , and health students 68 , 73 , 78 , 85 , 88 , 94 . Only six studies included a large sample of university students 44 , 66 , 69 , 84 , 86 , 97 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of high school students ranged from 13.2 (± 2.1) 70 to 16.9 (± 1.2) years 92 , while the mean age of university students ranged from 19.0 (± 1.1) 63 to 22.8 (± 3.0) years 63 . Most of the studies included a sample of medical students 63 65 , 67 , 76 , 79 , 81 , 82 , 87 , 89 , 93 , 96 nursing students 80 , 95 , and health students 68 , 73 , 78 , 85 , 88 , 94 . Only six studies included a large sample of university students 44 , 66 , 69 , 84 , 86 , 97 .…”
Section: Resultsmentioning
confidence: 99%
“…Depression was predictive of QOL Albani et al 80 Ghassab-Abdollahi et al 76 Miguel et al 82 QOL was predictive of depression Alvi et al 89 Depression is associated with low QoL/HRQL Angkurawaranon et al 64 Aqeel et al 88 Karuniawati et al 84 Blebil et al 83 Cleofas 44 Li et al 66 Pagnin and Queiroz 96 Pillay et al 65 Ratnani et al 63 Solanki et al 87 Tejoyuwono et al 81 QOL is negatively correlated with depression Markovic et al 73 Pekmezovic et al 97 Wen et al 86 Depression is associated with QoL in the psychological domain Borges et al 79 Burger et al 78 Depressive symptoms are associated with lower general QOL, except with the general health domain and social domain Gan and Rue 67 Depression is not correlated with physical functioning and pain Jenkins et al 94 Depression negatively impacts the physical and social domains Singh et al 69 Moderate symptoms of depression negatively affect the mental and physical components Souza et al 95 Depression is not correlated with physical functioning Moutinho et al 93 Depression is not correlated with QOL Armoon et al 68 Racic et al 85 Vol. :(0123456789) www.nature.com/scientificreports/ of QOL 64,67 , while a study with a sample of 193 Brazilian students indicated that the physical domain of QOL was unaffected by depression 96 .…”
Section: Qol Is Negatively Correlated With Depressionmentioning
confidence: 99%
“…Table 1 shows the study characteristics of the included studies comprising study population, study setting, study tool, study period, sample size and number of depressed undergraduate students along with ROB [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Figure 1: Prisma Flow Diagram Showing the Study Selection Pr...mentioning
confidence: 99%
“…The prevalence of depression in the nineteen studies ranged from 16.0% to 100.0%. The pooled prevalence of nineteen studies, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] 50.0% (95% CI: 31.0 to 70.0), was shown in Figure 2.…”
Section: The Pooled Prevalence Of Depressionmentioning
confidence: 99%
See 1 more Smart Citation